Consequences of information suppression in ecological and conservation sciences. Issue 1 (7th September 2020) - Driscoll, Don A.; Garrard, Georgia E.; Kusmanoff, Alexander M.; Dovers, Stephen; Maron, Martine; Preece, Noel; Pressey, Robert L.; Ritchie, Euan G.
Abstract: Suppressing expert knowledge can hide environmentally damaging practices and policies from public scrutiny. We surveyed ecologists and conservation scientists from universities, government, and industry across Australia to understand the prevalence and consequences of suppressing science communication. Government (34%) and industry (30%) respondents reported higher rates of undue interference by employers than did university respondents (5%). Internal communications (29%) and media (28%) were curtailed most, followed by journal articles (11%), and presentations (12%). When university and industry researchers avoided public commentary, this was mainly for fear of media misrepresentation, while government employees were most often constrained by senior management and workplace policy. One third of respondents reported personal suffering related to suppression, including job losses and deteriorating mental health. Substantial reforms are needed, including to codes of practice, and governance of environmental assessments and research, so that scientific advice can be reported openly, in a timely manner and free from interference.